DETERMINAN KEBIJAKAN LUAR NEGERI INDONESIA DALAM JOINT TRADE COMMITTEE (JTC) DENGAN MESIR PADA TAHUN 2023 - Ramadhani, Yoga; Safira, Putri Alyaa; Diphda, Bintang Corvi (Global and Policy Journal of International Relations, 2025)
This study explores the determining factors influencing Indonesia's foreign policy in the context of establishing the Joint Trade Committee (JTC) with Egypt in 2023. This research employs a qualitative approach with a case study design. The findings indicate that Indonesia’s foreign policy in forming the JTC with Egypt is driven by strategic economic calculations based on national strength, participatory domestic political dynamics, and international geopolitical opportunities. Indonesia actively utilizes a peaceful economic diplomacy approach to reinforce its position as a middle power that relies on soft power. The cooperation also reflects a strategic response to domestic pressures such as economic slowdown and a deliberate effort to diversify economic partnerships in the Middle East and North Africa (MENA) region. Therefore, the formation of the JTC shows a rational, adaptive, and long-term oriented foreign policy.